Formation of Prosocial Behaviour in the Process of University Liberal Education (Laisvalaikio tyrimai, 2018)
Research background. Today prosociality is an indisputably integral part of the prosperity of society. Analysing the complex and sophisticated issues of lifelong learning of a person, a holistic and high conceptual level theory of education is needed, which is based not only on the one-fold examination of the phenomenon of education, but also on a system of philosophy-based educational paradigms. Thus, liberal education is regarded as one of the essential and fundamental opportunities for the realization of higher education, thinking about the future of society. The above-mentioned aspects make the problematic question possible to be raised:  how is prosocial behaviour formed in the liberal education process at university? The article analyses the concept and essence of prosocial behaviour and examines the value basis of liberal education in order to reveal the possibilities of liberal education that determines prosocial behaviour at university.  R. Barnett’s (1990) liberal educational approach and conservative and radical concepts are used in this research. The aim was to reveal the formation of prosocial behaviour in the process of university liberal education. Method. The method of scientific literature analysis was used in the research in order to reveal the formation of prosocial behaviour during the liberal education process at university. Results and conclusions. The elements of the formation of prosocial behaviour are encoded in R. Barnett's (1990) liberal educational concepts that cannot exist separately, because the components of both concepts (development of critical thinking, freedom to make decisions, student self-expression, the ability to deal with moral dilemmas) actively and purposefully formulate human prosocial reasoning and behaviour .Keywords: liberal education, university, prosocial behaviour, higher education.